IMPACT INVESTING AND CLIMATE FINANCE: MEASURING SOCIAL RETURN ON INVESTMENT (SROI) IN RENEWABLE ENERGY PROJECTS - Ava Lee; Rachel Chan; Sanya Desai (Journal Markcount Finance, 2026)
This study examines the role of impact investing and climate finance in generating measurable social value through renewable energy projects by applying the Social Return on Investment (SROI) framework. Growing global investment in renewable energy has emphasized financial performance and emission reduction outcomes, while systematic measurement of social impacts remains limited. The purpose of this research is to assess how SROI can be used to quantify the social and environmental value created by renewable energy investments and to demonstrate its relevance for impact-oriented decision-making. A mixed-methods approach was employed, combining secondary project data analysis, stakeholder engagement, outcome mapping, and monetization of social and environmental benefits to calculate SROI ratios. The findings reveal that renewable energy projects consistently produce social returns exceeding the initial investment, with SROI ratios varying according to project type, scale, stakeholder involvement, and socio-economic context. Community-based and decentralized projects tend to generate higher relative social returns, driven by employment creation, improved energy access, health improvements, and environmental benefits. The study concludes that integrating SROI into climate finance evaluation enhances transparency, accountability, and alignment between financial objectives and sustainable development goals.